Effect of Plant Spacing on Yield and Yield Components of Tomato (Solanum lycopersicum L.) in Shewarobit, Central Ethiopia - Getachew Amare; Hailay Gebremedhin (Scientifica)
Inappropriate spacing is one of the major problems in tomato production at the study area. A field experiment was conducted to determine inter- and intrarow plant spacing for yield and yield components of tomato at Shewarobit, central rift valley of Ethiopia, under irrigation condition. The treatment comprises of three intrarow spacing (20, 30, and 40 cm) and four interrow spacing (60, 80, 100, and 120 cm) replicated three times and arranged in randomized complete block design using tomato variety Weyno. Data collected on fruit yield and yield components were analysed using SAS. The main effect of interrow spacing significantly affected marketable fruit, unmarketable fruit, marketable fruit number, unmarketable fruit number, and fruit diameter. The 20 cm interrow spacing showed a marked increase in marketable fruit yield by 35.96% as compared to 30 cm spacing used by farmers. Planting tomato in closer interrow spacing (60 cm) resulted in 50% yield increment than the widest (120 cm) space between rows. Interaction effects of both inter- and intrarow spacing significantly (p < 0.05) affected plant height and fruit length. An intrarow and interrow spacing of 20 ∗ 100 cm and 20 ∗ 120 cm resulted in tallest plants and widest fruits, respectively. Therefore, farmers can use 20 cm intrarow spacing and 60 cm interrow spacing for planting of tomato seedling of Weyno variety.